Field reports, Jim Sinclair, fall 1989 - Sinclair, Jimet al (1989)
Field reports form submitted by Jim Sinclair for fall 1989 with some detailed descriptions. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1989. Epson - sheet feed